ANALYSIS OF THE INFLUENCE OF PRODUCT QUALITY, SERVICE QUALITY AND LOCATION TO PURCHASE DECISIONS AT NDOWER VILLAGE NOODLES MOJOSARI, PUGER JEMBER DISTRICT - Ramadani, Resza; Rahayu, Jekti; Rusdiyanto, Rusdiyanto (Univesitas Muhammadiyah Tangerang, 2024)
In this era, lifestyle changes are increasingly occurring. The growth of culinary businesses is increasing along with changes in people's lifestyles and increasing people's incomes, especially in the community. The culinary business has become one of the businesses that is in great demand by people in Indonesia in recent years. Purchasing decisions are the main goal for business owners in a company. The purpose of this research is to find out how much influence product quality, product quality and location can influence purchasing decisions at ndower noodles in Mojosari village, Puger subdistrict, Jember. This type of research uses a quantitative research approach. The analytical method in this research is multiple liner regression analysis, the population in this research is ndower noodle customers in Mojosari village, Puger sub-district, Jember. The sample used was 105 respondents. The results of this research show that this conclusion is proven (1) product quality has a positive and significant effect on purchasing decisions. With a t count of 4.740 and a significance level of 0.00. (2) service quality has a positive and significant effect on purchasing decisions. With a t count of 3.089 and a significance level of 0.02. (3) location has a positive and significant effect on purchasing decisions. With a t count of 6.358 and a significance level of 0.00. The variables of product quality, service quality and location simultaneously have a positive and significant effect on purchasing decisions at Mie Ndower, Mojosari village, Puger sub-district, Jember.